(untitled) (Rev. Anal. Numér. Théor. Approx., 2001)
Book reviews for: Stephen J. Wright, Primal-dual interior-point methods, SIAM, Philadelphia, 1997, ISBN 0-89871–382-X, xv + 289 pp. Reviewed by A. Curseu. Desmond J. Higham and Nicholas J. Higham, Matlab Guide, SIAM, Philadelphia, 2000, ISBN 0-89871-469-9, xxii + 283 pp. Reviewed by E. Catinas. A. Griewank, Evaluating Derivatives. Principles and Techniques of Algorithmic Differentiation, Frontiers in Applied Mathematics Series no.19, SIAM, Philadelphia, 2000, ISBN 0-89871-451-6, xxiv + 369 pp. Reviewed by E. Catinas. C. Meyer, Matrix Analysis and Applied Linear Algebra, SIAM, Philadelphia, 2000, ISBN 0-89871-454-0, xii + 718 pp., Solutions Manual 171pp + CD. Reviewed by E. Catinas.